2020
DOI: 10.1038/s41598-020-70287-5
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic tree of Litopterna and Perissodactyla indicates a complex early history of hoofed mammals

Abstract: the Litopterna is an extinct clade of endemic South American ungulates that range from paleocene up to late Pleistocene times. Because of their unique anatomy, litopterns are of uncertain phylogenetic affinities. However, some nineteenth century authors, considered litopterns as related to perissodactyl ungulates, a hypothesis recently sustained by molecular data. The aim of the present contribution is to include litopterns and other South American related taxa in a comprehensive phylogenetic analysis together… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Buckley (2015) and Welker et al (2015) found that both Macrauchenia patachonica (Litopterna) and Toxodon platensis (Notoungulata) were part of the Perissodactyla on a proteomics-based analysis and Westbury et al (2017) recovered M. patachonica as sister to Perissodactyla, but on a mitochondrial genome-based study. Later, Chimento and Agnolin (2020) performed a morphologicalbased cladistic analysis and corroborated molecular proposals that litopterns and their kin (didolodontids and kollpaniids) were "successive stem clades of crown Perissodactyla." Very recently, MacPhee et al (2021) performed a morphologicalbased phylogenetic analysis recovering litopterns closer to perissodactyls than to other SANUs, i.e., a non-monophyletic SANUs, contrasting with the molecular proposals (Buckley, 2015;Welker et al, 2015).…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Buckley (2015) and Welker et al (2015) found that both Macrauchenia patachonica (Litopterna) and Toxodon platensis (Notoungulata) were part of the Perissodactyla on a proteomics-based analysis and Westbury et al (2017) recovered M. patachonica as sister to Perissodactyla, but on a mitochondrial genome-based study. Later, Chimento and Agnolin (2020) performed a morphologicalbased cladistic analysis and corroborated molecular proposals that litopterns and their kin (didolodontids and kollpaniids) were "successive stem clades of crown Perissodactyla." Very recently, MacPhee et al (2021) performed a morphologicalbased phylogenetic analysis recovering litopterns closer to perissodactyls than to other SANUs, i.e., a non-monophyletic SANUs, contrasting with the molecular proposals (Buckley, 2015;Welker et al, 2015).…”
Section: Introductionmentioning
confidence: 69%
“…Under this scenario, the SANUs remained blurred until Agnolin and Chimento (2011) suggest that some of them (Astrapotheria and Notoungulata) might be related to Afrotheria. This study shed light on to SANUs, bringing back the debate on their interrelationships within Eutheria (Billet and Martin, 2011;O'Leary et al, 2013;Kramarz and Bond, 2014;Buckley, 2015;Welker et al, 2015;Westbury et al, 2017;Chimento and Agnolin, 2020;MacPhee et al, 2021). Despite the heated debate, none of these studies included all lineages of SANUs (at least Litopterna, Didolodontidae, Astrapotheria, Notoungulata, Pyrotheria, and Xenungulata) and other Eutheria (at least Afrotheria and Laurasiatheria, the traditional "Ungulata") in the same phylogenetic analysis.…”
Section: Phylogenetic Relationships Of South American Native Ungulatesmentioning
confidence: 99%
See 1 more Smart Citation
“…South American) lineages that have a fossil record in the Paleogene of Europe, including reptiles (e.g., Augé & Brizuela, 2020;Scanferla & Smith, 2020b), as well as non-volant birds (Angst et al, 2013). In fact, faunal and floral exchanges between the Paleogene South American and African landmasses have been recently inferred for multiple different clades of non-marine animals and plants (e.g., Antoine et al, 2012;Aranciaga Rolando et al, 2019;Bond et al, 2015;Chimento & Agnolin, 2020;Croft, 2016;Katinas et al, 2013). The identification of Eoconstrictor as booid suggests that at least one of the large European constrictors had South American origin (Scanferla & Smith, 2020b), though of course, an African origin with subsequent dispersals to Europe and South America could also be the case (as it has been suggested for several South American mammal clades; see Croft, 2016).…”
Section: Palaeobiogeographymentioning
confidence: 99%
“…Modern proteomic (i.e., collagen) and mitochondrial DNA (mDNA) analyses support something of an intermediate between these two conflicting hypotheses; that is, there is a close Litopterna–Perissodactyla relationship, with the two groups, along with the Notoungulata, forming the monophyletic Panperissodactyla Welker et al, 2015 (see also Buckley, 2015; Westbury et al, 2017, for the mDNA study; and Chimento & Agnolin, 2020, for a phylogeny based upon skeletal data, but see Kramarz et al, 2021, for a critique of the latter study). The mDNA analysis additionally provided a means to infer the timing of the divergence of litopterns and perissodactyls, an event that appears to have occurred at about 66 Ma (range: 56.64–77.83 Ma), close to the Cretaceous–Paleogene (K–Pg) boundary (Westbury et al, 2017).…”
Section: Introductionmentioning
confidence: 99%